aMAP risk score predicts hepatocellular carcinoma development in patients with chronic hepatitis - Fan, Rong; Papatheodoridis, George; Sun, Jian; Innes, Hamish; Toyoda, Hidenori; Xie, Qing; Mo, Shuyuan; Sypsa, Vana; Guha, Indra Neil; Kumada, Takashi; Niu, Junqi; Dalekos, George; et al. (Journal of hepatology, 2020)
Hepatocellular carcinoma (HCC) is the leading cause of death in patients with chronic hepatitis. In this international collaboration, we sought to develop a global universal HCC risk score to predict the HCC development for patients with chronic hepatitis. A total of 17,374 patients, comprising 10,578 treated Asian patients with chronic hepatitis B (CHB), 2,510 treated Caucasian patients with CHB, 3,566 treated patients with hepatitis C virus (including 2,489 patients with cirrhosis achieving a sustained virological response) and 720 patients with non-viral hepatitis (NVH) from 11 international prospective observational cohorts or randomised controlled trials, were divided into a training cohort (3,688 Asian patients with CHB) and 9 validation cohorts with different aetiologies and ethnicities (n = 13,686). We developed an HCC risk score, called the aMAP score (ranging from 0 to 100), that involves only age, male, albumin–bilirubin and platelets. This metric performed excellently in assessing HCC risk not only in patients with hepatitis of different aetiologies, but also in those with different ethnicities (C-index: 0.82–0.87). Cut-off values of 50 and 60 were best for discriminating HCC risk. The 3- or 5-year cumulative incidences of HCC were 0–0.8%, 1.5–4.8%, and 8.1–19.9% in the low- (n = 7,413, 43.6%), medium- (n = 6,529, 38.4%), and high-risk (n = 3,044, 17.9%) groups, respectively. The cut-off value of 50 was associated with a sensitivity of 85.7–100% and a negative predictive value of 99.3–100%. The cut-off value of 60 resulted in a specificity of 56.6–95.8% and a positive predictive value of 6.6–15.7%. This objective, simple, reliable risk score based on 5 common parameters accurately predicted HCC development, regardless of aetiology and ethnicity, which could help to establish a risk score-guided HCC surveillance strategy worldwide. In this international collaboration, we developed and externally validated a simple, objective and accurate prognostic tool (called the aMAP score), that involves only age, male, albumin–bilirubin and platelets. The aMAP score (ranged from 0 to 100) satisfactorily predicted the risk of hepatocellular carcinoma (HCC) development among over 17,000 patients with viral and non-viral hepatitis from 11 global prospective studies. Our findings show that the aMAP score had excellent discrimination and calibration in assessing the 5-year HCC risk among all the cohorts irrespective of aetiology and ethnicity. [Display omitted] •In total, 17,374 patients with viral and non-viral hepatitis from 11 global prospective cohorts/trials were studied.•An HCC risk score (called the aMAP score, ranging from 0 to 100), which involves only age, male, albumin–bilirubin and platelet data, was developed and validated.•The aMAP score had excellent discrimination and calibration in assessing the 5-year HCC risk irrespective of aetiology and ethnicity.•Patients with aMAP score <50, accounting for 44% of overall population, had an HCC incidence of <0.2% per year.